علامہ علی بن الحسین المسعودي كي سيرت نگاري کا مطالعہ: Seerah Writing of Abū al-Ḥasan ʿAlī ibn al-Ḥusayn ibn ʿAlī al-Masʿūdī. An analytical Study - Aleem Khan; Dr. Muhammad Sajjad (MEI, 2023)
Allama Abu al Hassan Ali bn al Hussain al Masudi(957AD) Was a great historian and Geographer.As a tourist, he visited almost all eastern countries of the world. During his such visits, he wrote accounts of memories regarding personalities , geography, culture and traditions of different nations in a number of books which unfortunately, misplaced except his two books namely " Murooj uz-Zahab wa Ma'adin ul-Jauhar" and " Kitāb al-tanbīh wa al-Ashrāf" . Both the books have short account of the life of the Holy Prophet ( Peace be upon him ). This article is a survey of historical and Biographical charactristics of author’s sira writing along with study of both texts. The first book deals with world history and goegraphy including brief Sira account and Islamic History till 236 AH. The later also includes history, topography, astronomy, culture and traditions of different world nations including Prophtic stories , Sira of the Holy Prophet(SAW) and Islamic history till 245 AH.